Role of Pharmacognosists in Regulating Herbal Industry - Chandrashaker K.S (Journal of Global Pharma Technology, 2018)
Herbal medicines are widely used all over the world for the treatments of various diseases. Hence regulation is necessary for herbal medicinal products. Different countries have different regulation for herbal medicinal products. Standardization is an important part of regulation in which raw material and finished products specification, analytical and in process methods, stability study are required. In this article herbal products and its regulatory requirements are discussed. This is useful for marketing herbal medicinal products particularly in India.Keywords: Herbal medicines, Chromatogram, Ayurvedic drugs.